Flow and mixing of elongated particles in rotating drums of different sizes - Song, Jinhua; Naeem, Numan; Fan, Hu; Li, Guanhua; Li, Maosong; Guo, Yu; Lin, Jianzhong; Tie, Jinxin (Frontiers in Chemical Engineering, 2025)
A numerical study is performed using the Discrete Element Method (DEM) to investigate flow and mixing of elongated particles in rotating drums. Spherical particles and their mixtures have been extensively explored in the previous work, while the present study focuses on the elongated rod-like particles and binary mixtures of the elongated particles with two different aspect ratios. Different drum sizes are used to examine scale-up behaviors in such dynamic processes. For both monodisperse and binary particle systems, dynamic angle of repose is determined mainly by a Froude number Fr, measuring the ratio of centrifugal force to gravitational force on a particle, while it is insensitive to scale-up ratio α, defined as the ratio of cross-sectional areas of the current drum to the reference one. Average particle velocity and contact force generally increase with both Froude number and scale-up ratio. Mixing rate of the particles is significantly promoted by increasing Fr, and it maintains constant at small Fr and decreases slowly with increasing α at large Fr. Some differences are observed between the monodisperse and binary systems: i) The mixing index eventually achieves the same high level for all the monodisperse systems, while the final mixing indices are smaller with smaller Fr for the binary systems; ii) The mixing rate of the binary mixtures has a stronger dependence on the scale-up ratio α than the monodisperse systems; iii) With increasing α, the average contact force increases for the monodisperse systems while it changes non-monotonically at large Froude numbers for the binary systems.